Perlindungan Hukum Terhadap Pembeli Yang Beritikad Baik Atas Objek Yang Belum Bersertifikat - Zefanya Cheryl Loru Koba (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Buying and selling is one of the most common agreements in everyday life. However, in some cases, not all objects of sale and purchase meet the complete formal or administrative requirements, for example with the existence of immovable property objects that have not been certified. Problems arise if the party dealing with this case is a good faith buyer, because he has the potential to lose his rights to the object that has been purchased. Thus, this research aims to find out what are the criteria for good faith buyers and legal protection for good faith buyers of objects that have not been certified. This research is a legal research using 2 (two) approach methods, namely statutory and conceptual approaches. The result of this research is that the criteria for a good faith buyer is when the buyer buys and sells the land object with legal procedures and documents as determined by laws and regulations and takes care by researching matters relating to the agreed land object. While the form of legal protection that can be given to a good faith buyer is the recognition of ownership of the uncertified sale-purchase object on the condition that the current proves that he has met the criteria of a good faith buyer.